CHALLENGES OF CONTEMPORARY COMPANIESAND THE CONCEPT OF "HEROIC LEADERSHIP" - Lachytová, Lenka; Mazur, Piotr; Depa, Dorota (Revista Inclusiones, 2020)
Modern companies face new challenges in terms of how to manage and define expectations for their employees. Socio-economic changes cause that the employees are expected not only to have specialist knowledge of their job, but also to be willing to take responsibility, make decisions or participate in decision-making process, independent creation of solutions and self-control. The structures of companies are becoming more and more flat, which means that the roles of employees’ self-management skills and cooperation between them are increasing. How to create a work environment so that people are ready to meet these expectations? What rules to follow so that the hired employee is personally involved in achieving the company’s goals? This article presents the concept of "heroic leadership" based on four principles, which were shaped and implemented by members of the Society of Jesus for almost 500 years. This leadership model stands in opposition to those based on the concept of "one big man". It assumes that everyone can be a leader. The role of Jesuit"managers" was to equip the team members with such skills that they would know what to do to ensure that everyone achieves "high goals".